Приближенная аналитическая модель пограничного слоя вокруг нейтронной звезды со слабым магнитным полем при дисковой аккреции - Бисноватый-Коган, Г. С.
We have constructed an approximate one-dimensional model of the boundary layer for the disk accretion around the neutron star with a low enough magnetic field, not influencing the accretion process. We consider the high luminosity model with radiation dominated equation of state.
Keywords: Астрофизика